Upaya Meningkatkan Pemahaman Siswa Kelas VIII.E Melalui Penggunaan Media Google Classroom dalam Pembelajaran Jarak Jauh IPA Materi Organ Ekskresi Semester Genap Tahun Pelajaran 2021/2022 - Lisma Heryati (Departement of Mathematics Education, 2022)
This study aims to describe the benefits of using Google Classroom (GC) as an alternative distance learning media during the COVID-19 pandemic. The type of research used in this research is descriptive research with One Shot Case Study design. The subjects in this study were students of Class VIII.E science subjects on excretory organs material in the even semester of the 2021/2022 academic year, totaling 30 people. The instrument that has been used in this research is a test of student learning outcomes. Analysis of the data used is descriptive analysis using SPSS 16 for windows. The results showed that there was a significant effect on student learning after learning using Google Classroom (GC) media was applied. This is indicated by the average score of student learning outcomes of 80 which is in the high category.